1999
DOI: 10.1016/s0194-5998(99)70181-6
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of reflux therapy on pediatric chronic sinusitis

Abstract: After reflux treatment, the number of children requiring sinus surgery was dramatically reduced. The results of this preliminary pediatric study indicate that gastronasal reflux should be evaluated and treated before sinus surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
1
9

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(109 citation statements)
references
References 21 publications
1
98
1
9
Order By: Relevance
“…Eighteen excluded publications were case series, studying CRS response to GORD treatment (8)(9)(10)(11)(12)(13)(14) , GORD pathogenesis in CRS (8,12,13,(15)(16)(17)(18)(19) , and epidemiological association between GORD and CRS (20)(21)(22)(23)(24)(25) .…”
Section: Search Resultsmentioning
confidence: 99%
“…Eighteen excluded publications were case series, studying CRS response to GORD treatment (8)(9)(10)(11)(12)(13)(14) , GORD pathogenesis in CRS (8,12,13,(15)(16)(17)(18)(19) , and epidemiological association between GORD and CRS (20)(21)(22)(23)(24)(25) .…”
Section: Search Resultsmentioning
confidence: 99%
“…An alternative theory of pathogenesis proposes the existence of a reflex response such as has been described with GER and pulmonary disease. 12 Such an esophagonasal or esophagonasopharyngeal reflex that causes sinonasal mucosa to respond to esophageal irritation has not been demonstrated.…”
Section: Commentmentioning
confidence: 99%
“…These same theories may also apply to chronic sinusitis. Bothwell et al [33] showed that 75% of children with chronic sinusitis had abnormal pH testing, and in 25/28 children sinus symptoms improved with medical antirefl ux treatment. Similar results have been found in adults [34][35][36] .…”
Section: Additional Head and Neck Manifestations Of Eermentioning
confidence: 99%